(untitled) (Dhaka University Journal of Applied Science and Engineering, 2022)
Handover is crucial for data portability, real-time data generation, and data processing in mobile technology. Up to 4G, handover efficiency reached optimal stability. However, with the entrance of 5G, the cellular network has turned into a complete heterogeneous network (HetNet) with enormous diversity due to the integration of Internet of Things (IoT) devices with mobile networks. Resource-constrained IoT devices differ notably in operational features from traditional mobile devices. Those devices usually need a smaller geographical cell with better connectivity coverage than conventional large cells of the same size. Hence, to support IoT, 5G splits large geographical cell areas into small cells and allows bandwidth sharing during Device-to-Device (D2D) communication. In a nutshell, 5G infrastructures and architectures have been changed a lot from the previous generations, and handover needs to be re-thought for efficient mobility management. This paper has incorporated the concept of Software-defined Network (SDN) in a 5G cellular network to simplify HetNet and provide efficient handover management within it. We illustrate our proposed handover management concept within this simplified HetNet that utilizes idle time scanning and preauthentication to reduce handover delay. The experimental implementation shows a significant 42% delay optimization during inter-domain reactive handover with 50% less communication overhead than the existing scheme. DUJASE Vol. 6 (2) 49-58, 2021 (July)